2003
DOI: 10.33899/rden.2003.165762
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial profile of patient with missing teeth and refuses treatment

Abstract: This study aimed to assess the psychosocial and medical factors that are related to refusal of prosthetic replacement, as well as to give a treatment for such problem. Also the number and distribution of missing teeth in partially edentulous individuals according to Kennedy classification was evaluated, as well as to assess the prevalence of Kennedy classification in partially edentulous patients in rural areas.The study was conducted in Al-Humaidat village that is located at the Tigris river about 25 Km to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Curtis et al reported that mandibular removable partial dentures are more common than maxillary removable partial dentures, and that the class I mandibular RPD is the most prevalent type of RPD for either dental arch. 9 Kennedy Class III was reported to be the most common pattern (57.14%) in a sample of the Iraqi population in a study carried out by Hatim et al 27 In Benin, Ehikhamenor, et al 28 found that the most commonly restored edentulous area was Kennedy's class III (57.3%). In this study, Kennedy's Class III was found to be the most prevalent pattern of partial edentulism both in the maxillary arch (44.9%) and the mandibular arch (67.4%).…”
Section: Discussionmentioning
confidence: 95%
“…Curtis et al reported that mandibular removable partial dentures are more common than maxillary removable partial dentures, and that the class I mandibular RPD is the most prevalent type of RPD for either dental arch. 9 Kennedy Class III was reported to be the most common pattern (57.14%) in a sample of the Iraqi population in a study carried out by Hatim et al 27 In Benin, Ehikhamenor, et al 28 found that the most commonly restored edentulous area was Kennedy's class III (57.3%). In this study, Kennedy's Class III was found to be the most prevalent pattern of partial edentulism both in the maxillary arch (44.9%) and the mandibular arch (67.4%).…”
Section: Discussionmentioning
confidence: 95%
“…(12) Similar findings have been revealed by other studies. (8,13) Nevertheless, contrasting results were reported by a researcher who found class IV and class I predominant ones. (14) In this study, there was no significant association between Kennedy's class and arch type (p=0.09).…”
Section: Discussionmentioning
confidence: 95%
“…In this study, Kennedys class III is the most prevalent pattern of partial edentulousness which is similar to the previous study conducted in the Nepalese population, 12,[14][15][16] and similar results were obtained in a previous study conducted in the Iraqi population. 17,18 This could be attributed to the fact that the first molar is the first permanent tooth to erupt into the oral cavity and has a higher chance of being affected by caries and a greater likelihood of the tooth being extracted. 19 However, few studies have shown Class I as the most prevalent type of partial edentulism in their study.…”
Section: Discussionmentioning
confidence: 99%